Aspirin intervention before ICU admission reduced the mortality in critically ill patients with acute kidney injury: results from the MIMIC-IV - Meng, Yao; Lin, Yi; Zhang, Jia-Wei; Zou, Wen-Li; Liu, Yue-Ming; Shen, Xiao-Gang; Shen, Quan-Quan; Wang, Min-Min; Shao, Li-Na; Feng, Hong-Yuan; Zhu, Yan; Yu, Jing-Ting; et al. (Frontiers in Pharmacology, 2023)
Background: Aspirin, with its pleiotropic effects such as anti-inflammatory and anti-platelet aggregation, has been widely used for anti-inflammatory, analgesic, and cardiovascular diseases. However, the association between the use of aspirin before the intensive care unit (ICU) and clinical outcomes in critically ill patients with acute kidney injury (AKI) is unknown.Methods: Patients with AKI in this retrospective observational study were selected from the Marketplace for Medical Information in Intensive Care IV (MIMIC-IV). The association between aspirin intervention and 30-day mortality was assessed using Cox proportional hazards model. Logistic regression models were used to assess the association of aspirin intervention with the risks of intracranial hemorrhage, gastrointestinal bleeding and blood transfusion. The propensity score matching (PSM) method was adopted to balance the baseline variables. Sensitivity analysis was performed to validate the results by multiple interpolations for the missing data.The study included 4237 pre-ICU aspirin users and 9745 non-users. In multivariate models, we found a decreased risk of mortality in those who received aspirin before ICU compared to those who did not (30-day:hazard ratio [HR], 0.70; 95% CI, p<0.001;0.70; 95%CI,p<0.001; 0.72;95%CI, p<0.001). This benefit was consistent in the post-PSM analyses, sensitivity analyses, and subgroup analyses. Moreover, aspirin intervention was associated with a reduced risk of intracranial hemorrhage and gastrointestinal bleeding (HR, 0.16; 95% CI, p<0.001; HR, 0.59; 95% CI, p=0.012) after being adjusted by relating covariates, whereas with a increased risk of blood transfusion (HR, 1.28; 95% CI, p<0.001).Patients with AKI treated with aspirin before ICU admission might have reduced 30-day,90-day and 180-day mortality without increasing the risk of intracranial hemorrhage (ICH) or gastrointestinal bleeding, but may increase the risk of transfusion.